BIOETHANOL PRODUCTION FROM COCONUT HUSK USING THE WET GAMMA IRADIATION METHOD - Putra Oktavianto; Risdiyana Setiawan; Ilhami Ariyanti; Muhammad Fadhil Jamil (BATAN, 2020)
BIOETHANOL PRODUCTION FROM COCONUT HUSK USING the WET GAMMA IRRADIATION METHOD. The use of coconut husk has only been used as a material for making handicrafts such as ropes, brooms, mats, and others or just burned. The combustion of coconut husk can cause air pollution. In fact, coconut husk can be used as a raw material for bioethanol production so that the beneficial value of coconut husk will also increase. One way of bioethanol production from coconut husk is by irradiating the coconut husk. The coconut husk irradiation technique to be carried out in this study is the wet irradiation technique. Wet irradiation is carried out to accelerate the process of bioethanol production because at the time of irradiation, cellulose has been hydrolyzed and glucose has been formed so that it is more efficient in time and use of the material so that the cellulose hydrolysis process is not necessary. The coconut husk samples were wet because they were mixed with 4% NaOH and were irradiated using a gamma irradiator from STTN-BATAN Yogyakarta with a dose of 30 kGy and 50 kGy and 0 kGy (or without irradiation). Then the sample is fermented with the fungus Saccharomyces Cerevisiae from tape yeast to form ethanol. Ethanol is purified and then analyzed for concentrations using pycnometric and refractometric methods. The result is that the highest ethanol content is without irradiation (0 kGy), this is due to the low dosage used. However, the main point in this wet method research is evidence of hydrolysis of cellulose by the formation of gluoxane after irradiated wet coconut husk, and with Fehling A and B analysis, brown deposits are seen proving that glucose has been formed.